El Salvador : Second Review Under the Stand-By Arrangement-Staff Report; Informational Annex; Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The development of macroeconomic performance in El Salvador in the second half of 2010 was broadly positive, but economic activity remains subdued. The medium-term economic outlook has been revised to incorporate changes to the external environment since the first program review. The economic program for 2011 will adhere to the fiscal consolidation path envisaged in the Stand-By Arrangement (SBA). Higher tax revenue will be critical for attaining the fiscal target. Placing the public debt-to-GDP ratio on a downward path and increasing social spending on a sustained basis remain the key priorities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet